Evaluation of civil society projects in countries with high HIV prevalence: a methodological discussion - DOI: 10.3395/reciis.v1i2.82en - Wilza Vieira Villela; Rosemary Barden Maarden (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
This article approaches methodological aspects of the evaluation of community projects in countries where HIV/AIDS prevalence is high, from the assumption that these countries need to adjust epidemic reduction actions to development initiatives. It originates from work carried out in the Republic of Mozambique in 2006 , in which 160 of the 1124 civil society projects supported by the government were evaluated, with a focus on their relevance, design quality, efficiency, intervention quality, coverage, supervision, organizational capacity, and support received from the government. In order to set a value for the performance of each project, with an eye to the differences in each of the various organizations and of the context in which they were developed, a system of variables and indicators, composed of quantitative and qualitative information, collected by means of questionnaires, interviews, visits to the projects and document analysis was designed, which proved adequate for the purposes of the work. It is considered that the evaluation of the civil society interventions in poor countries, and other places where the epidemics are disseminated, must be guided by tools capable of intercepting the challenges generated from the combination of AIDS, poverty, and culture, so as to build an operational understanding of the socio-cultural and economic factors which contribute to the success or failure of community initiatives for combating the epidemics.